Eksplorasi Etnomatematika Geometri pada Arsitektur dan Lingkungan Pantai Sejarah Kabupaten Batubara: Pendekatan Deskriptif Kualitatif - Saragih, Sisca Sri Dewi; Siregar, Khofifa Romaito; Hasibuan, Hokkop Efendi; Putri, Nayla Aiwina (Media Pendidikan Matematika, 2025)
Ethnomathematics is an approach that examines the relationship between mathematics and cultural practices in everyday life. Natural environments and traditional architectural structures contain rich forms and patterns that can be analyzed through mathematical concepts, particularly geometry. This study aims to explore the representation of geometric concepts found in the architectural structures and natural surroundings of Pantai Sejarah Batubara. A descriptive qualitative approach was employed, using observations, documentation, and informal interviews with local communities and site managers as data collection techniques. The findings reveal the presence of various geometric forms such as rectangles, squares, triangles, circles, cubes, blocks, prisms, and natural spirals in gazebos, entrance gates, wave breakers, ocean wave patterns, and mollusk shells. These results indicate that Pantai Sejarah Batubara holds significant potential as a contextual learning resource for geometry through an ethnomathematical perspective. This study contributes to the development of culturally grounded and environmentally based mathematics learning.